1991
DOI: 10.1111/j.1349-7006.1991.tb01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Combined Antitumor Effect of Natural Human Tumor Necrosis Factor‐α and Natural Human Interferon‐α on Cell Cycle Progression

Abstract: We have studied the mechanism of the synergistic effect of the combination of tumor necrosis factor‐α (TNF‐α) and interferon‐a (IFN‐α) on cell cycle progression using two‐parameter flow cytometry in vitro and an immunohistochemical staining method in vivo. The cells used were human colon cancer cell line RPMI 4788 in vitro and in vivo, and human breast cancer cell line MX‐1 and human renal cancer cell line NAMKO‐1 in vivo. In the in vitro experiment, the cell cycle progressed normally as time elapsed in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…We also investigated the involvement of various protein kinases and phosphatases in the early (0-4 h) signal transduction events induced by TNFa. Previous studies addressing the cell cycle specificity of TNFa action have concluded that this cytokine blocks the progression of the cell cycle at the post-synthetic G2 or M phases (Darzynkiewicz et al, 1984;Dealtry et al, 1987;Muro et al, 1991). However, these studies employed cell lines which responded to TNFa exposure with cell lysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the involvement of various protein kinases and phosphatases in the early (0-4 h) signal transduction events induced by TNFa. Previous studies addressing the cell cycle specificity of TNFa action have concluded that this cytokine blocks the progression of the cell cycle at the post-synthetic G2 or M phases (Darzynkiewicz et al, 1984;Dealtry et al, 1987;Muro et al, 1991). However, these studies employed cell lines which responded to TNFa exposure with cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that TNFx inhibits the growth of various cancer cell lines in vivo by both a cytolytic and a cytostatic mechanism (Sugarman et al, 1985;Fransen et al, 1986, Browning & Ribolini, 1989. Previous studies have indicated that cells which are lysed by TNFa are first blocked at the postsynthetic G2, M phases of the cell cycle, and that cells accumulating in S or M phases subsequently undergo cell death (Darzynkiewicz et al, 1984;Dealtry et al, 1987;Muro et al, 1991). Several cellular mechanisms have been proposed to explain the cytolytic effect of TNFa (for review: Larrick & Wright, 1990).…”
mentioning
confidence: 99%
“…31 Another report showed that activated NF-kB exhibited opposite functions following induction by different treatments in a single cell line; NF-kB activation induced by combined treatment with PMA and ionomycin was proapoptotic in a T-cell hybridoma cell line, whereas glucocorticoid-induced NF-kB was antiapoptotic in the same cells. 35 TNF/IFN-a induced a cytotoxic response in certain tumors, [18][19][20] and also had crosstalk interactions in immune responses. 36 We therefore investigated whether NF-kB activation induced by TNF/IFN-a, had an antiapoptotic or proapoptotic effect.…”
Section: Discussionmentioning
confidence: 99%
“…2,18 Recently, we reported that TNF/IFN-a combined treatment inhibited the in vitro and in vivo proliferation of human colon adenocarcinoma cells. 19,20 Previous reports demonstrated that TNF-activated NF-kB has an antiapoptotic effect. [21][22][23][24][25] Beg et al 21 showed that TNF treatment of fibroblasts and macrophages from RelA-deficient (RelA À/À ) mice resulted in a significant reduction in viability, whereas RelA +/+ cells were unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…The TNF-␣ Japan reference (lot no. JPR5 KO1) was used as a standard (5). We first tested the effect of serial injections of high-dose M-CSF in a BCG-LPS-challenged murine model.…”
mentioning
confidence: 99%